Blended Learning with Flipped Classroom through Contextual Teaching and Learning Approach to Increase Motivation and Learning Outcomes - Rahmadi Rahmadi (VANOS Journal of Mechanical Engineering Education, 2022)
This study aims to determine the increase in learning motivation and learning outcomes in technical drawing lessons for class X TKRO 3 SMKN 1 Bulakamba students in the even semester of the 2021/2022 academic year. This research is a classroom action research conducted in two cycles, where each cycle consists of four stages, namely: planning, implementing action, observing, and reflecting. Learning in the first cycle was carried out by blended learning with a flipped classroom, while the learning in the second cycle was carried out by blended learning with a flipped classroom using a contextual teaching and learning approach. Sources of data were obtained from 36 students of class X TKRO 3, learning motivation data was obtained from questionnaires via google form while learning outcomes data were obtained from formative test scores and worksheet scores. Processing and data analysis using Microsoft Excel 2010. The results showed that in the initial conditions students who had high/very high learning motivation were 22, in the first cycle there were 29 and in the second cycle 33. While the average value of the initial conditions, the first cycle was 33. I, cycle II was 79, 81, 82 with the percentage of passing respectively 72.2%, 77.8%, 91.7%. Learning motivation increased by 31.8% in the first cycle and 13.8% in the second cycle, while the average value of learning outcomes increased by 2.53% in the first cycle and 2.47% in the second cycle.